RISK ANALYSIS OF SHARIA BANK FINANCING CONTRACT - Riduwan, Riduwan; Danupranata, Gita (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2020)
Non-Performing Financing (NPF) is the inability of customers to meet their obligations in accordance with the contract, which can be categorized into three types namely substandard, doubtful and bad debt (macet). NPF is the main and biggest risk for sharia banks, hence the ability of sharia banks to identify, measure, monitor and control the risks of financing and capital provision is very important. Sharia banks will face greater risks than conventional banks because of the risk of sharia reputation. Besides being influenced by internal and external factors of sharia banks, NPF can also be influenced by the financing contract (akad) used.This study analyzes the level of financing risk based on the contract. The population and sample are all Sharia Rural Banks in Indonesia with 167 secondary data in the form of the publication of financial statements for 2011-2018. Analysis of the data using quantitative descriptive methods with a survey approach. The analyzed data are NPF data based on an eight year financing contract. This study managed to obtain data that the BPRS is more interested in financing with certainty of results, proven that murabahah has the highest outstanding compared to other contract. The results of this study also indicate that the low risk contract is in the murabahah contract, while the contract with the medium risk is in the mudarabah, musyarakah, multijasa, qard and istisna and the contract with the highest risk is salam and ijarah contract.